MENINGKATKAN KECERDASAN MUSIK ANAK MELALUI KEGIATAN BERMAIN DENGAN ALAT PERKUSI SEDERHANA DI RA NURUL HUDA SARANG BURUNG DENAI PANTAI LABU - Widodo (CV. Arsy Persada Quality, 2025)
The results of observations before conducting research regarding the initial conditions before the research, showed that children who developed very well and developed according to expectations in the activities studied, namely, paying attention to and understanding explanations about playing percussion instruments reached 25%, carrying out activities playing percussion instruments according to directions reached 31, 2%, playing percussion instruments without assistance reached 37.5%, the suitability of music with playing percussion instruments reached 31.2%. From the overall results of the assessment on observation activities before the research, it was 31.2%. The results of the research in the first cycle were children who developed very well and developed according to expectations in the activities studied, namely, paying attention to and understanding explanations about playing percussion instruments reaching 50%, carrying out activities playing percussion instruments according to directions reached 50%, carrying out activities of playing percussion instruments without assistance reached 50%, suitability of music with playing percussion instruments reached 43.7%. This shows that children's musical intelligence increased to 48.4%. And the results of the research in the second cycle were children who developed very well and developed according to expectations in the activities studied, namely, paying attention to and understanding explanations about playing percussion instruments reaching 81.2%, carrying out activities playing percussion instruments according to directions reaching 75%, carrying out play activities unassisted percussion instruments reached 81.2%, the suitability of music with playing percussion instruments reached 75%. This shows that children's musical intelligence has increased to 78.1%. Based on the results of research on all cycles starting from cycle 1 - cycle 2, it was found that the increase in children's musical intelligence through the activity of playing simple percussion instruments was from before conducting the research, the average ability of children reached 31.2%, the first cycle rose to 48.4%, and the second cycle rose to 78.1% . Thus, it can be stated that increasing children's musical intelligence through the activity of playing simple percussion instruments at RA Nurul Huda has been successful.